Financial innovation : too much or too little? - Haliassos, Michael (MIT Press, 2013)
This text, which includes two contributions from Robert Shiller as well as a discussion of Shiller's 'MacroMarkets' tool, considers the key ingredients of financial innovation from both academia and industry; the postive potential but also the risks of financial innovation and the influence of producers on consumers.